2018
DOI: 10.1016/j.jfi.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Does competition aggravate moral hazard? A Multi-Principal-Agent experiment

Abstract: We conduct a Multi-Principal-Agent experiment to determine whether market structure affects intermediary behavior. The intermediaries (Agents) are perfectly informed regarding project types and can recommend that Principals either proceed or discontinue with a project. Agents earn revenues only when they recommend to continue. We find that monopolist Agents protect the interests of Principals better than when Agents compete. Our findings are robust to a significant fee increase. The results of our study apply … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Yet another strand of experimental studies suggests that even strong nancial incentives hardly interfere with agents' attempt to adhere to their clients' preferences (see, e.g.,Rud et al, 2018;Ifcher and Zarghamee, 2019;Kling et al, 2019).…”
mentioning
confidence: 99%
“…Yet another strand of experimental studies suggests that even strong nancial incentives hardly interfere with agents' attempt to adhere to their clients' preferences (see, e.g.,Rud et al, 2018;Ifcher and Zarghamee, 2019;Kling et al, 2019).…”
mentioning
confidence: 99%
“…Such a ‘race to the bottom’ could occur in terms of lower service quality, not apparent to the customer, or in lowering of ethical standards. Shleifer (2004) provides a number of examples of this across a range of industries, while Egan et al (2019) and Rud et al (2018) are among recent papers examining the effect of competition on moral standards in the financial sector. Di Maggio et al (2016) find evidence of a ‘race to the bottom’ in terms of predatory lending upon the relaxation of regulation in the USA, which is more pronounced in areas where higher competition prevailed.…”
Section: Community Standards and Expectations And Competitionmentioning
confidence: 99%
“…Flannery and Roberts [28] found that nonmonotonic contracts with incentives are more conducive to resolving the principal-agent problem. Rubin and Sheremeta [29] and Rud et al [30] discussed the influence of competition on the moral hazard in the principal-agent relationship and pointed out the role of managerial labor market on personal incentives and equilibrium results.…”
Section: Introductionmentioning
confidence: 99%